Clinical Outcomes of TU-LESS Combined with Extracorporeal Operation in Benign Adnexal Masses: A Retrospective Study - Wang, Yanyan; Sun, Binzhou; Hu, Yanqiong; Wang, Tingting; Ge, Luqian (Journal of the Pakistan Medical Association, 2026)
Objective: To investigate the clinical effect of transumbilical laparoendoscopic single-site surgery integrated with extracorporeal operation mode for treating benign adnexal masses. Method: The retrospective study was conducted in October 2024 at the Maternity and Child Care Centre, Qinhuangdao, China, and comprised data of female patients with benign adnexal masses admitted from January 2022 to September 2024. The patients were randomised into two groups, with group A controls receiving conventional multi-port laparoscopic surgery, and intervention group B undergoing transumbilical laparoendoscopic single-site surgery with extracorporeal surgical mode. Intraoperative condition, postoperative rehabilitation, complication incidence, inflammatory cytokine levels and quality of life scores were compared between the groups. Data was analysed using SPSS 25. Results: Of the 60 female patients, 30(50%) were in group A having mean age 32.38±5.21 years, and the remaining 30(50%) were in group B with mean age 32.38±5.21 years. There was no significant intergroup difference between the groups at baseline (p>0.05). There was no significant difference in intraoperative bleeding and surgical time between the groups (p>0.05). Group B showed significantly shorter postoperative anal exhaust time, ambulation time and hospitalisation duration as well as lower complication rates compared to group A (p<0.05). The average levels of interleukin-6, high-sensitivity C-reactive protein and tumour necrosis factor-alpha in group B were lower than those in group A 24 hours after surgery (p<0.05). The quality of life was higher in group B than group A (p<0.05) Conclusion: The transumbilical laparoendoscopic single-site surgery integrated with extracorporeal operation mode could reduce surgical trauma, shorten postoperative recovery process, inhibit inflammatory response, and improve patients' quality of life. Key Words: Transumbilical laparoendoscopic single-site surgery, Extracorporeal operation mode, Traditional multi-port laparoscopic surgery, Benign adnexal mass, Postoperative rehabilitation, Complications, Quality of life.